Efficacy of astragalus polysaccharides (PG2) in alleviating chemotherapy-induced fatigue in gynecologic cancer: a retrospective cohort study - Chia-Ching Chang; Yi-Liang Lee; Chih-Hsiang Yin; Cheng-Chang Chang; Yi-Hsin Lin (Discover Oncology)
Abstract Background Cancer related fatigue (CRF) is a common and debilitating side effect among gynecologic cancer patients undergoing chemotherapy. Astragalus polysaccharides (PG2), an immunomodulatory drug, has shown promise in relieving CRF. This study aimed to evaluate the effectiveness of PG2 in managing CRF in gynecologic cancer patients. Methods This retrospective cohort study was performed at the Department of Obstetrics & Gynecology, Tri-Service General Hospital from December 2015 to December 2022. Of 53 patients included, 40 received PG2 with chemotherapy, while 13 received chemotherapy alone. Outcomes included CRF severity and HRQL, assessed via Brief Fatigue Inventory (BFI) and Functional Assessment of Cancer Therapy-General 7 (FACT-G7), plus safety profiles. Results PG2-treated patients showed a statistically significant reduction in CRF severity, as reflected by lower BFI (p < 0.001). The PG2 group showed trends toward improved HRQL and reduced appetite loss, though not statistically significant (p > 0.05). PG2’s safety profile aligned with the control group, showing no increase in grade 3/4 toxicities. Conclusion The study concludes that PG2 shows promise as an adjunct therapy in the management of CRF among patients with gynecologic cancer receiving chemotherapy. However, the findings highlight the need for additional prospective, randomized controlled trials to rule out the risk of bias and ascertain PG2’s full therapeutic potential in oncology supportive care.